The role of affect in attitude formation toward new technologies: The case of stratospheric aerosol injection - Christine Merk; Gert Pönitzsch (Kiel Institute for the World Economy (IfW), 2016)
This paper analyzes determinants of technology acceptance and their interdependence. It highlights the role of affect in attitude formation toward new technologies and examines how it mediates the influence of stable psychological variables on technology acceptance. Based on theory and previous empirical evidence, we develop an analytical framework of attitude formation. We test this framework using survey data on the acceptance of stratospheric aerosol injection (SAI), a technology that could be used to counteract global warming. We show that affect is more important than risk and benefit perception in forming judgment about SAI. Negative and positive affect directly alter the perception of risks and benefits of SAI and its acceptability. Furthermore, affect is an important mediator between stable psychological variables - like trust in government, values, and attitudes - and acceptance. A person's affective response is thus guided by her general attitudes and values.
Keywords: 330; technology acceptance; stratospheric aerosol injection; climate engineering; affect; attitudes; values; trust